Effect of cefodizime, ofloxacin, ciprofloxacin and Interferon cela, alone and in combination, on phagocytic and candidacidal functions of leucocytes from patients with chronic renal failure - (:unkn) unknown (My University, 1999)
We have examined the effects of cefodizime, ofloxacin, ciprofloxacin and Interferon a-2a (IFNa-2a), alone and in combination, on phagocytosis and killing of Candida albicans blastospores by polymorphonuclear leucocytes (PMNs) from patients with chronic renal failure. The effects of therapeutic concentration of each drug on the phagocytic and candidacidal capacity were studied in vitro. 20 chronic renal failure patients, average age 45, were included. Phagocytosis and candidacidal capacity were significantly enhanced (P < 0.001 ) after pre-treatment of PMNs with cefodizime at 10 ug/ml, but ofloxacin (4 ug/ml) and IFNa-2a (10 U/ml) had no effect compared to the control with no antibiotics. However, only candidacidal capacity increased significantly with ciprofloxacin at 2 ug/ml (P < 0.001). In contrast, ciprofloxacin had no significant effect on phagocytosis (P > 0.05). Combinations of these three drugs with IFNa-2a produced the same effect as these two drugs alone. These results indicate that cefodizime, ofloxacin and ciprofloxacin alone and in combination with IFNa-2a at safely achievable concentrations generally do not suppress PMN function in vitro. © 1999 Lippincott Williams & Wilkins.
Keywords: Cefodizime; Chronic renal failure; Ciprofloxacin; Interferon a-2a; Ofloxacin; Phagocytic and candidacidal function